Detection of microspheres in vivo using multispectral optoacoustic tomography. (2nd January 2017) - Bhutiani, N; Kimbrough, CW; Burton, NC; Morscher, S; Egger, M; McMasters, K; Woloszynska-Read, A; El-baz, A; McNally, LR
Abstract: We introduce a new approach to detect individual microparticles that contain NIR fluorescent dye by multispectral optoacoustic tomography in the context of the hemoglobin-rich environment within murine liver. We encapsulated a near infrared (NIR) fluorescent dye within polystyrene microspheres, then injected them into the ileocolic vein, which drains to the liver. NIR absorption was determined using multispectral optoacoustic tomography. To quantitate the minimum diameter of microspheres, we used both colorimetric and spatial information to segment the regions in which the microspheres appear. Regional diameter was estimated by doubling the maximum regional distance. We found that the minimum microsphere size threshold for detection by multispectral optoacoustic tomography images is 78.9 µm.